Detection of Escherichia coli and staphylococcus aureus as indices of sanitary quality of pre-cut pinakbet vegetables sold in selected sidewalk markets - Cortes, Emily Paje (2000)
ABSTRACT Raw pr-cut vegetables for "pinakbet" were purchased from 5 sidewalk markets in Quezon City. The samples were examined for Escherichia coli and Staphylococcus aureus. These two organisms served as the indices of sanitary uality of the samples. The samples were obtained from Balara, BF Homes, Krus na Ligas, Manggahan, and Tandang Sora during regular market hours. This study was accomplished using 3 phases that included determination of the sampling population, microbial examination of the vegetable samples, and assessment of the sanitary quality of the handling pocedures. Results of the microbial examination showed that all samples underwent unhygienic cutting, handling and selling conditions. This is indicated by their positive tests for coliforms and Staphylococcus aureus. The biochemical test done confirmed the presence of Escherichia coli in all samples suggesting, fecal contamination. All the samples greatly exceeded the acceptable microbial criteria of 2 x 10 raise to 2 MPN/g sample for coliform. They had an average count of 1.1 x 10 raise to 3 MPN/g. the occurrence of Staphylococcus aureus in the vegetable samples was also established which can be explained by the handling of the vegetables with bare hands. The S. aureus count showed that the vegetable sample displayed uncovered in the open markets were the most heavily contaminated. The sample bought pre-packed gave relatively low counts of S. aureus, indicating that the main sources of contamination of these organisms are the unclean hands of the food handlers and vendors, as well as the air, dust and insects hovering this food product.